1953
DOI: 10.1139/v53-124
|View full text |Cite
|
Sign up to set email alerts
|

THE THERMAL DECOMPOSITION OF n-BUTANE

Abstract: The thermal decomposition of n-butane at 442 °C.has been investigated analytically in the pressure range 4–13 cm. Up to 9% decomposition, the rates of formation of H2, CH4, C2H4, and C2H6 are independent of time; the dependence of the rates on butane pressure was approximately first order. The validity of the extrapolation procedure for obtaining the initial products was established, there being no significant variation in the composition of the products with extent of decomposition. In the nitric oxide fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1954
1954
1973
1973

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The present investigation has confirmed this behaviour. Some investigators (4,5,72) have reported that the molar quantities of ethylene produced were generally higher than those of ethane. They did not believe that the secondary process involving ethane dehydrogenation could account for this result and therefore concluded that the reaction:…”
Section: Resultsmentioning
confidence: 99%
“…The present investigation has confirmed this behaviour. Some investigators (4,5,72) have reported that the molar quantities of ethylene produced were generally higher than those of ethane. They did not believe that the secondary process involving ethane dehydrogenation could account for this result and therefore concluded that the reaction:…”
Section: Resultsmentioning
confidence: 99%
“…Coupled with the present excess supply, this will add to the pressure to find new outlets for n-butane. Earlier investigations into the pyrolysis were conducted by Pease and Durgen (1930), Nehaus and Marek (1932), Steacie and Puddington (1938), Crawford and Steacie (1953), Hepp and Frey (1953), and Wang, et al (1963). In these and other early studies, the products were seldom measured at conversions of butane below 10%.…”
mentioning
confidence: 99%
“…A similar phenomenon was next found in the decomposition of normal pentane (Danby, Spall, Stubbs & Hinshelwood 1954), though the detailed investigation in * Recently, Crawford & Steacie (1953) have studied the thermal decomposition of n-butane and state that the relative proportions of the products from the uninhibited reaction (in volving chains) are different from those of the nitric-oxide-inhibited reaction, and quote the results of Stubbs et at. (1952) in support of this.…”
mentioning
confidence: 60%